Measuring and mapping leaf chlorophyll content with Konica Minolta SPAD-502 and ARCMAP 10.3 / Nur Afiqah Mohd Rodzi - Mohd Rodzi, Nur Afiqah (Faculty of Plantation and Agrotechnology, 2018)
The study was conducted at Kampung Tersusun Seri Mendapat, Semujuk Melaka. The purpose of the study is to measure nitrogen (N) using Konica Minolta SPAD-502 in 3 stages to determine the distribution of leaf N and displayed the map using ArcMap. Konica Minolta SPAD-502 is a non-destructive device which is a lightweight handheld meter for measuring the chlorophyll content of leaves without causing damage to plants. If the data was conducted in a lab then it will cause time and cost consuming. Therefore, a non-destructive method was used. The result showed in 3 stages N can be measured using SPAD meter and illustrated through ArcMap. By observing the map, it will demonstrate the distribution of leaf N which what plot contain high and low amount of N. By using the graph, it showed the 3 stages of SPAD data value trend of data. As a conclusion, it can be concluded that the reading between 3 stages of leaf chlorophyll displayed at some plot occurred low reading of N at the first data taken and the last data reading occurred higher.